Higher Dietary Se Intake Is Associated With the Risk of New-Onset Fracture: A National Longitudinal Study for 20 Years - Zhang, Yangchang; Ye, Mengliang; Zhao, Yong; Xiong, Yang; Shen, Shisi; Yu, Qiuhua; Lu, Yanjun; Shi, Zumin; Lei, Xun (Frontiers in Nutrition, 2021)
Background: The association between dietary selenium (Se) intake and osteoporosis-related fractures remains controversial. The present study aimed to examine the dose-relationship between Se intake and incident fracture among Chinese adults. Methods: The dietary data were retrieved from the China Health and Nutrition Survey during in 1991 and 2011, and 17,150 participants aged above 20 were included. Cumulative average intake of dietary Se was assessed by a three-day 24-hour review of food. Fracture was based on self-report in surveys between 1997 and 2015. Cox regression was used to examine the association. The non-linear association was examined by restricted cubic splines (RCS). Results: There were 976 fracture cases during a mean of 10.2 years follow-up. Se intake was associated with incident fracture. In fully adjusted model, across quartiles of Se intake, the hazard ratios (HRs) for fracture were 1.07 (95%CI 0.86-1.33), 1.00 (reference), 1.25 (95%CI 1.02-1.53) and 1.33 (95%CI 1.07-1.65), respectively. RCS showed a parabolic association (P non-linear=0.037) between Se and fracture for men as well as a U-shape dose-response (P non-linear=0.04) between Se and fracture for subjects living in highly urbanized areas. Conclusion: In conclusion, high intake of dietary Se is positively associated with incident fracture among Chinese adults. Along with increased Se intake, there would be a parabolic increment of fracture risk for the males, and a U-shape fracture risk for people in the high urbanization level.